2020
DOI: 10.1177/1528083720901864
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanical, thermal, and acoustical behaviors of cotton, polyester, and cotton/polyester nonwoven wastes reinforced epoxy composites

Abstract: The aim of this paper is to develop a textile waste-based composite material with adequate mechanical, acoustical, and thermal properties for automotive or construction fields. For this purpose, three recycled nonwoven wastes including cotton, polyester, and cotton/polyester blend are employed and blended in epoxy resin. The manufacturing of the composite panels is performed by vacuum infusion technique. Mechanical, thermal and acoustical tests are conducted to characterize the performances of both nonwoven fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…159,160 Fibrous textile waste can be used as reinforcement in polymeric composites, in the form of waste fabric, shoddy (fibres obtained from waste textiles), converting to yarn, woven or nonwoven fabric, and producing micro or nanofillers . [161][162][163][164][165][166] Studies have shown that polymeric composites reinforced with textiles waste can be employed in building and construction . 167 So, industrial textile waste (both synthetic and natural fibres) will also be used as reinforcement in the polymer matrix to improve the end products' functional and structural qualities by changing the parameters such as combine fibres of diverse nature, chemical composition, and size.…”
Section: Role Of Industrial Textiles In Polymer Compositementioning
confidence: 99%
“…159,160 Fibrous textile waste can be used as reinforcement in polymeric composites, in the form of waste fabric, shoddy (fibres obtained from waste textiles), converting to yarn, woven or nonwoven fabric, and producing micro or nanofillers . [161][162][163][164][165][166] Studies have shown that polymeric composites reinforced with textiles waste can be employed in building and construction . 167 So, industrial textile waste (both synthetic and natural fibres) will also be used as reinforcement in the polymer matrix to improve the end products' functional and structural qualities by changing the parameters such as combine fibres of diverse nature, chemical composition, and size.…”
Section: Role Of Industrial Textiles In Polymer Compositementioning
confidence: 99%
“…Some of the most important advantages of these technologies are productivity (compared to traditional craft), and flexibility (can produce various products for various applications fields). 17,18 S. Lukic and P. Jovanic designed new composite material based on non-woven textile material (NTM). They have used Latex as a bonding agent and Al 2 O 3 particles as abrasive components of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…The strong interfacial interaction between fibers of cotton and the molecular structure of epoxy provided enhanced mechanical strength. 43 In addition, because of a wide scope for the epoxy/cotton material, recently a modal study has been conducted by Lu et al 44 to develop a real-time 3D needled composite. However, no significant studies have been done about the surface behavior of epoxy-coated cotton and about its application in oil-water separation.…”
Section: Introductionmentioning
confidence: 99%